2005
DOI: 10.1097/01.gim.0000151150.20570.e7
|View full text |Cite
|
Sign up to set email alerts
|

Telegenetics in Maine: Successful clinical and educational service delivery model developed from a 3-year pilot project

Abstract: Purpose: The goal of this 3-year pilot project was to increase accessibility to genetics educational and clinical services in Maine. Methods: Southern Maine Genetics Services, Foundation for Blood Research in collaboration with Maine Telemedicine Services established telemedicine capacity to link with rural health care centers located in Northern, Central, and Southern Maine and public health nursing statewide for the provision of genetics clinical and educational services. Core partners included a rural famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 11 publications
4
121
0
1
Order By: Relevance
“…24,27,37 Of the 125 patients who were evaluated and/or counseled via telemedicine in the study by Lea et al, 37 64% received pediatric and/or neurological genetics consultations and the rest received consultations for cancer or reproductive genetics counseling. Pediatric telegenetics services often included physical examinations, whereas consultations for cancer generally only involved a review of the patients' family history, the provision of information, and psychosocial support.…”
Section: Results Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…24,27,37 Of the 125 patients who were evaluated and/or counseled via telemedicine in the study by Lea et al, 37 64% received pediatric and/or neurological genetics consultations and the rest received consultations for cancer or reproductive genetics counseling. Pediatric telegenetics services often included physical examinations, whereas consultations for cancer generally only involved a review of the patients' family history, the provision of information, and psychosocial support.…”
Section: Results Study Characteristicsmentioning
confidence: 99%
“…Eight of the studies did not have a comparison group, and reported data solely on those who received genetics services via a telemedicine. 24,26,[29][30][31][32][35][36][37][38] All the studies measured patient satisfaction with the telegenetics consultation; in some cases, the health professionals' satisfaction was also assessed. The methods of measuring satisfaction varied between studies, with many researchers developing their own scales of satisfaction, whereas others based their scales on previous research.…”
Section: Results Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations